2019
DOI: 10.1111/jpn.13055
|View full text |Cite
|
Sign up to set email alerts
|

Potential toxicity of cyanogenic glycoside amygdalin and bitter apricot seed in rabbits—Health status evaluation

Abstract: Amygdalin is one of the most studied secondary metabolites of Prunus genus. It is a cyanogenic glycoside which was initially obtained from the bitter almonds seeds and is a major component of the seeds of plants, such as apricots, almonds, peaches, apples and other rosaceous plants. The views of scientists on the use of amygdalin have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Clinical symptoms of acute cyanide poisoning, which usually occur less than 1 min after inhalation and within a few minutes after ingestion, include rapid respiration, a drop in blood pressure, rapid pulse, headache, dizziness, vomiting, abdominal pain, diarrhea, mental confusion, stupor, blue discoloration of the skin due to lack of oxygen (cyanosis), twitching and convulsions to coma and death [19][20][21]. A series of poisoning cases (adults, children, livestock) has been reported from the ingestion of bitter apricot kernels [21][22][23][24][25][26][27][28]. Long-term exposure to sublethal concentrations of cyanogenic glycosides can present ongoing health issues, such as Konzo, an irreversible motor neuron disease with clinical signs including the inability to walk, limited arm movement, and speech difficulties [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms of acute cyanide poisoning, which usually occur less than 1 min after inhalation and within a few minutes after ingestion, include rapid respiration, a drop in blood pressure, rapid pulse, headache, dizziness, vomiting, abdominal pain, diarrhea, mental confusion, stupor, blue discoloration of the skin due to lack of oxygen (cyanosis), twitching and convulsions to coma and death [19][20][21]. A series of poisoning cases (adults, children, livestock) has been reported from the ingestion of bitter apricot kernels [21][22][23][24][25][26][27][28]. Long-term exposure to sublethal concentrations of cyanogenic glycosides can present ongoing health issues, such as Konzo, an irreversible motor neuron disease with clinical signs including the inability to walk, limited arm movement, and speech difficulties [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…After consumption of apricot or bitter almond seeds, hydrogen cyanide can be produced in high enough level to pose a possible chronic toxicity problem (Miller et al, 1981;Tušimová et al, 2017). According to Shragg, Albertson, and Fisher (1982), amygdalin may be 40 times more toxic by peroral way as compared to intravenous or intramuscular application (Casarett, Doull, Klaassen, & Amdur, 1980;Kováčiková et al, 2019). According to Shragg, Albertson, and Fisher (1982), amygdalin may be 40 times more toxic by peroral way as compared to intravenous or intramuscular application (Casarett, Doull, Klaassen, & Amdur, 1980;Kováčiková et al, 2019).…”
mentioning
confidence: 99%
“…Moertel et al (1981) observed that different ways of amygdalin administration play an important role in organism. According to Shragg, Albertson, and Fisher (1982), amygdalin may be 40 times more toxic by peroral way as compared to intravenous or intramuscular application (Casarett, Doull, Klaassen, & Amdur, 1980;Kováčiková et al, 2019). Therefore, the Food Drug Administration (FDA) banned to sale of amygdalin as a natural medication.…”
mentioning
confidence: 99%
“…Amygdalin is one of the main biologically active substances present in apricot seeds, hot almonds, flax seeds, and others (Tanwar et al, 2019). The effect of AMG present in apricot seeds has been partially described in our previous studies using the porcine model (Halenar et al, 2015), rabbits (Halenar et al, 2017;Kolesar et al, 2018;Kovacikova et al, 2019) and humans (Kopčeková et al, 2018;Kovacikova et al, 2017). The objective of this study was to evaluate the effects of apricot seeds on microscopic characteristics of rabbit liver in vivo.…”
Section: Resultsmentioning
confidence: 91%
“…The field of nutritional research focuses on phytonutrients and their beneficial properties on health. Phytonutrients, which include in particular polyphenols, flavonoids (isoquercitrin, rutin, quercetin, and others) (Roychoudhury et al, 2018;Kolesarova et al, 2019), ellagitannins, especially punicalagin and ellagic acid (Packova et al, 2015), glycosides (amygdalin) (Halenar et al, 2015(Halenar et al, , 2017Kolesar et al, 2018;Kopcekova et al, 2018;Kovacikova et al, 2019) and others are known to possess potential antioxidant and antitumor activity and the ability to eliminate environmental stress-induced reprotoxicity (Kolesarova et al, 2012;Halenar et al, 2015). Cancer is a major public health problem worldwide and is the second leading cause of death in the United States (Siegel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%